Fortified Jaggery: A Pathway to Functional and Nutraceutical Foods - Kumar Pandeya, Arvind; Garima, Garima; Paroha, Seema; Srivastava, Vishnu Prabhakar (Journal of Neonatal Surgery, 2025)
Jaggery, a traditional non-centrifugal sugar, is emerging as a promising carrier for fortifying functional and nutraceutical foods. This review examines how jaggery's nutritional value can be enhanced by incorporating essential micronutrients, herbal extracts, and bioactive compounds. It also discusses processing techniques such as vacuum impregnation and osmotic dehydration, focusing on their effects on nutrient retention and sensory properties. Additionally, the health benefits of fortified jaggery are explored, including its role in managing anemia, boosting the immune system, and promoting gut health. The review highlights the challenges of large-scale production, regulatory considerations, and future prospects for fortified jaggery as a functional food product.